PENGARUH SUASANA TOKO DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN SEBAGAI TEMPAT WORK FROM CAFE PADA GERAI KOPI KENANGAN 24 JAM DI POS PENGUMBEN JAKARTA BARAT - Zisilia Nurhaliza Jawas; Nurul Aisyah; Chodidjah (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the influence of store atmosphere and service quality on customer satisfaction as a Work From Cafe (WFC) venue at the 24-Hour Kopi Kenangan Outlet in Pos Pengumben, West Jakarta. This research is motivated by the growing phenomenon of work from cafe, which has transformed cafes not only as places to eat but also as spaces for working and studying. In this context, store atmosphere and service quality become important factors that can influence customer satisfaction. The theoretical framework of this study refers to the store atmosphere theory by Berman and Evans, service quality by Tjiptono, and customer satisfaction by Kotler and Keller. This study uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling technique. Data were analyzed using multiple linear regression with IBM SPSS Statistics 20. The results show that store atmosphere has a positive and significant effect on customer satisfaction (t = 2.963; sig. = 0.004), service quality has a positive and significant effect on customer satisfaction (t = 7.840; sig. = 0.000), and both variables simultaneously have a positive and significant effect on customer satisfaction (F = 255.365; sig. = 0.000). The coefficient of determination of 84.0% indicates that customer satisfaction can be explained by store atmosphere and service quality. Service quality is the most dominant variable influencing customer satisfaction